2011
DOI: 10.3109/15563650.2011.569932
|View full text |Cite
|
Sign up to set email alerts
|

Communication patterns for the most serious poison center calls

Abstract: Context The communication demands faced by specialists in poison information (SPI) are challenging in the health care context. Objectives 1: Describe SPI communication patterns for the highest risk poison exposure calls using cluster analysis, and 2: describe variation in communication patterns or clusters. Methods A sample of 1 year of poison exposure calls to a regional PCC with SPIs’ perceived severity rating of major/moderate perceived was collected. Digital voice recordings were linked with medical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…1, high call volume periods are unpredictable and uncommon events, making them difficult to study. In order to systematically evaluate the potential impact of high volume call periods on PCCs, we used data collected for a larger study 35 to identify the most active periods (99th percentile) of SPI activity as high volume time based on call volume. We evaluated five statistical models (probability distributions) and found that the Weibull distribution for “calls per SPI per 30-minute period” most consistently identified time periods that were busier than 99% of all other time periods.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1, high call volume periods are unpredictable and uncommon events, making them difficult to study. In order to systematically evaluate the potential impact of high volume call periods on PCCs, we used data collected for a larger study 35 to identify the most active periods (99th percentile) of SPI activity as high volume time based on call volume. We evaluated five statistical models (probability distributions) and found that the Weibull distribution for “calls per SPI per 30-minute period” most consistently identified time periods that were busier than 99% of all other time periods.…”
Section: Discussionmentioning
confidence: 99%
“…35 All calls to the emergency hotline were routed to an automatic call distributor (ACD) that “answers” the call and a descriptive option menu is played for the caller. When the caller selects the “poisoning or overdose” option, the call is routed to ring on the phone of an available SPI.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The choice of communication methods and channels of communication perceived by the user are critical in influencing the use of PCC services (Ellington et al, 2011). Additionally, Kshatri et al (2021) stated that the readily available and easily accessible effective communication channels are essential to enhance awareness and utilization of services.…”
Section: Communication Channelsmentioning
confidence: 99%